Numerical investigation of solar panel orientation for optimal power generation and drag performance on a VLEO satellite - Ling, Merrick Tong Le (Nanyang Technological University, 2024)
This research paper delves into the field of small satellites (SmallSats) operations in the very low Earth orbit (VLEO) environment. With orbital altitudes ranging below 450km, the VLEO environment offers numerous advantages for satellite missions in the form of optimising mission performances, reducing overall mission costs, contributing to space sustainability efforts, and more.